OBSERVATIONS ON THE CHAETOGNATHA OF THE WATERS AROUND MANDAPAM - Sudarsan, D (Indian Journal of Fisheries, 2011)
DIFFERENT species of organisms belonging to diverse groups hke diatoms, medusae, pteropods, chaetognaths and tunicates that occur in the plankton are known to be indicators of the water-masses and changing hydrological conditions and of those, chaetognaths have been successfully used in many regions during recent times. Further, the chaetognaths take their place in the food cycle of the sea as predators, competitors and prey in relation to the other constituents of the marine animal community and hence the importance of their study cannot be overemphasised